2011
DOI: 10.1111/j.1464-5491.2010.03195.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of insulin therapy amongst Asian patients with diabetes in Singapore

Abstract: Insulin refusal is an important problem amongst our patients with Type 2 diabetes mellitus. Findings of this study suggest that interventions aimed at increasing insulin therapy use should focus on injection-related concerns, perceived lifestyle adaptations and correction of misconceptions. Different interventions may also be required for patients of different educational groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 22 publications
(29 reference statements)
4
79
4
3
Order By: Relevance
“…(4) In a study conducted by Wong et al in Singapore, 70.6% of the patients expressed unwillingness to use insulin therapy. (5) A study conducted on Bangladeshi patients in East London who had poorly controlled T2DM showed that 42.5% refused insulin therapy when it was first prescribed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) In a study conducted by Wong et al in Singapore, 70.6% of the patients expressed unwillingness to use insulin therapy. (5) A study conducted on Bangladeshi patients in East London who had poorly controlled T2DM showed that 42.5% refused insulin therapy when it was first prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies from Malaysia and Singapore involved patient populations that consisted of well-urbanised city dwellers. (4,5) …”
Section: Introductionmentioning
confidence: 99%
“…14 Previous studies conducted in western countries have identified several factors that can lead to PIR. [11][12][13] These reasons might differ in Asian countries, however. 15,16 Recently, a local primary care research group developed a scale, Chinese Attitudes to Starting Insulin questionnaire, to identify barriers to insulin initiation in insulin-naïve patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…10 Their reluctance to initiate insulin use [10][11][12] and its subsequent titration 13 is known as 'psychological insulin resistance' (PIR). The prevalence of PIR has been estimated to be higher in Singapore (70.6%) 11 than in western countries (approximately 20%-40%). 12 A HK survey of 97 participants found a similarly high prevalence of PIR (72.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation